Prove that (sec4theta- sec2 ) = tan4theta+
tan2thetha
with detail explanation only
what happens there
Attachments:
Answers
Answered by
0
Answer:
L.H.S.
sec4θ - sec2θ
= sec2 θ [ sec2 θ - 1 ] { taking sec2 θ as common }
= sec2θ * tan2θ { * = multiply.}
R.H.S.
tan4θ +tan2θ
= tan2θ [ tan2θ + 1 ]
= tan2θ * sec2θ
or sec2θ * tan2θ
= > L.H.S. = R.H.S.
Answered by
0
Answer:
your answer
Step-by-step explanation:
PLEASE LIKE SHARE AND SUBSCRIBE TO MY YOUTUBE CHANNEL OF TOTAL GAMING.......
Attachments:
Similar questions